PENGARUH CAPITAL INTENSITY, SALES GROWTH, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENGINDARAN PAJAK: (Studi Empiris pada perusahaan Manufaktur Subsektor Makanan dan Minuman yang terdaftar di BEI periode 2017-2021) - Azis, Azzy Abdul; Sari, Intan Rahma (Transpublika Publisher, 2022)
This research seeks to investigate and give empirical data about the partial and simultaneous effects of capital intensity, sales growth, and institutional ownership on tax avoidance. The population of this research consists of food and beverage firms that are listed on the Indonesia Stock Exchange. This inquiry utilizes previously gathered information. Using a method of stratified sampling, data was acquired. This investigation's sample consists of twelve firms. Five years are being discussion, from 2017 to 2021. Multiple linear regression analysis with Eviews version 9 is the method of data analysis used here. According to the study's findings, there is a high correlation between tax evasion and the amount of business capital intensity and institutional ownership, but not with sales growth. Tax evasion is significantly influenced by concurrent study on topics like sales growth, capital intensity, and institutional ownership.